Analysis of Strategies to Improve the Quality of Budget Performance Information using Logic Models - Riyan Nur Ramadhan; Deddi Nordiawan (Budapest International Research and Critics University, 2022)
This research discusses the analysis of strategies to improve the quality of Budget Performance Information using logic models framework in implementing the Redesign of Planning and Budgeting Systems, which will be carried out in all institutions starting in the 2021 fiscal year. Other researchers have found that redesigning the planning and budgeting system is insufficient to create an effective and efficient budget. The problem is that the performance information inscribed in planning and budgeting documents is still challenging to understand from internal and external institutions. The question in this study is about strategies to improve the quality of the formulation of Programs, Activities, Outputs, and Outcomes by using a logical model in government institutions X. The performance information between the Output of the Activity and the Output of the Program with the Outcomes can lead to less logical and non-mutually supportive without using a logical model framework. The research method used was a qualitative descriptive case study. Data collection is through document analysis and interviews with parties directly involved in the core process. The analysis results show that logical models have not been the leading framework in planning and budgeting. It is also that not all parties related to the process understand the logical model framework. The results imply that the use of logical models sufficiently affects the quality of the resulting budget performance information.